Draft Ninth Five Year Plan 1997-2002 (Revised) Government of Gujarat - Planning Commission (Planning Commission, 1997)
Gujarat has an area of 196024 sq. kms. which is about 5.96 percent of the Indian Union. Its population in 1991 was 4.13 crore which constitutes nearly 5 percent of the Country's total population and was predominantly rural-65.5 percent. The average density of population was 211 persons per sq. km. The size of the main working force in 1981 was 109.84 lakh, out of which 60.11 percent were provided employment under agriculture while the size of the main working force in 1991 was 140.96 lakh, out of which 56.29 percent were provided employment under agriculture. The remaining 43.71 percent of the main working- force was engaged in manufacturing, household industry, trade and commerce and other activities.
Government of Gujarat, General Administration Department (Planning Division)